1981
DOI: 10.1002/jrs.1250110302
|View full text |Cite
|
Sign up to set email alerts
|

The vibrational spectrum of the benzophenone molecule

Abstract: The vibrational spectrum of the benzophenone molecule has been studied using Raman spectroscopic techniques. The assignment of the observed bands has been supported by a normal mode calculation. Special attention has been paid to the interpretation of the low-frequency modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The corresponding ground state vibrational frequencies were calculated by Blazevic and Colombo [48] to be 45 and 50 cm À1 . The present theoretical calculation also yields nearly the same result.…”
Section: Species [1] Ramanmentioning
confidence: 99%
“…The corresponding ground state vibrational frequencies were calculated by Blazevic and Colombo [48] to be 45 and 50 cm À1 . The present theoretical calculation also yields nearly the same result.…”
Section: Species [1] Ramanmentioning
confidence: 99%
“…A large number of investigations have been performed recently in order to study structural, electronic, polarization characteristics and vibrational spectra of benzophenone derivatives [2][3][4][18][19]. Vibrational modes of benzophenone/substituted benzophenones have also been discussed by various researchers in different phases such as vapor, liquid and crystals [20][21][22][23]. Several spectroscopic, polarization absorption properties and UV electronic transition studies of halogen and methyl substituted benzophenone have been reported in the literature [24][25][26][27][28] from time to time.…”
Section: Introductionmentioning
confidence: 99%
“…30,50,51 While most Raman active modes of benzophenone exhibit no dependence on solvent structure, there are two features which are an exception to this rule. These modes comprise the carbonyl stretch, denoted ν(C=O), which is found over a relatively broad region around 1662.8 ± 7.2 cm −1 and the aromatic stretching modes ν i (C-H) in the vicinity of ∼3066 cm −1 (Fig.…”
Section: A Solvatochromic Shiftsmentioning
confidence: 90%